Practice Effect of Repeated Cognitive Tests Among Older Adults: Associations With Brain Amyloid Pathology and Other Influencing Factors - Zheng, Bang; Udeh-Momoh, Chinedu; Watermeyer, Tamlyn; de Jager Loots, Celeste A.; Ford, Jamie K.; Robb, Catherine E.; Giannakopoulou, Parthenia; Ahmadi-Abhari, Sara; Baker, Susan; Novak, Gerald P.; Price, Geraint; Middleton, Lefkos T. (Frontiers in Aging Neuroscience, 2022)
Background: Practice effects (PE), after repeated cognitive measurements, may mask cognitive decline and represent a challenge in clinical and research settings. However, an attenuated practice effect may indicate the presence of brain pathologies. This study aimed to evaluate practice effects on the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) scale, and their associations with brain amyloid status and other factors in a cohort of cognitively unimpaired older adults enrolled in the CHARIOT-PRO SubStudy. Methods: 502 cognitively unimpaired participants aged 60-85 years were assessed with RBANS in both screening and baseline clinic visits using alternate versions (median time gap of 3.5 months). We tested PE based on differences between test and retest scores in total scale and domain-specific indices. Multiple linear regressions were used to examine factors influencing PE, after adjusting for age, sex, education level, APOE-ε4 carriage and initial RBANS score. The latter and PE were also evaluated as predictors for amyloid positivity status based on defined thresholds, using logistic regression. Results: Participants’ total scale, immediate memory and delayed memory indices were significantly higher in the second test than in the initial test (Cohen’s dz = 0.48, 0.70 and 0.35, P < 0.001). On the immediate memory index, the PE was significantly lower in the amyloid positive group than the amyloid negative group (P = 0.022). Older participants (≥ 70 years), women, non-APOE-ε4 carriers, and those with worse initial RBANS test performance had larger PE. No associations were found between brain MRI parameters and PE. In addition, attenuated practice effects in immediate or delayed memory index were independent predictors for amyloid positivity (P < 0.05). Conclusion: Significant practice effects on RBANS total scale and memory indices were identified in cognitively unimpaired older adults. The association with amyloid status suggests that practice effects are not simply a source of measurement error but may be informative with regard to underlying neuropathology.